Prevalence and Associated Factors of Severe Preeclampsia Among Pregnant Women - Kunawati Tungga Dewi (Bulletin of Inspiring Developments and Achievements in Midwifery, 2025)
In Indonesia, the incidence of preeclampsia is around 5.3% or 128,273 per year. In addition, preeclampsia is still accounts for 26.9% of maternal deaths in Indonesia. Purpose : This research attempts to analyze factors associated with the prevalence of severe preeclampsia in pregnant women at Dr. M. Djamil Padang Hospital. Methods : This study took a cross-sectional approach and employed an analytical design. The sample consisted of 200 pregnant women taken using the systematic random sampling method from a total population of 705 patients. In July, data gathering was completed 2024 from medical records and examined using the chi-square test both univariately and bivariately. Result : The results showed that age (p = 0.006), parity (p = 0.001), history of preeclampsia (p = 0.005), and pregnancy spacing (p = 0.001) were significantly associated with the incidence of severe preeclampsia. However, obesity (p=0.923) showed no significant relationship. Implications : These findings imply the need for healthcare providers to prioritize early education and screening for pregnant women at risk due to age, parity, history of preeclampsia, and pregnancy spacing, in order to reduce the prevalence of severe preeclampsia and prevent further maternal and fetal complications. Conclusions: It is recommended that health workers increase prevention efforts through education and counseling on the risk of preeclampsia in pregnant women.